Eviction and rent in taxes Islam issued (Journal of the College of Basic Education, 2022)
Through the foregoing, we find that rent and rent were used in the taxes of the Sassanids and the Byzantines, but it was not apparent except in a simple manner at the end of the Rashidun Caliphate, then it developed after that in the Umayyad Caliphate and continued widely in the Abbasid Caliphate. These procedures result in the following: